ANALISIS PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN - Nailal Husna (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2016)
The object of this study is a banking company whose shares are listed in Indonesia Stock Exchange 2011-2014 period, and the sampling method was census. The purpose of this study was to determine the effect of the financial performance of banking shares. And the research variables are Stock Price (Y), Return on Assets (X1), Debt to Equity Ratio (X2), Price Earning Ratio (X3), Earning Per Share (X4). Based on the analysis and discussion of the results of testing the hypothesis then the conclusion is Price Earning Ratio and Earning Per share, positive and significant impact on the share price, while Return on Assets, Dept To Equity Ratio, Earnings Per share no significant effect on stock price. Keywords : Stock Price, Return on Assets, Debt To Equity ratio, Price Earning Ratio, Earnings Per Share, Bank